The Influence of Risk Perception, Project Uncertainty, and Investment Appraisal Techniques on Capital Budgeting Decisions: A Systematic Literature Review - Anggia Marshanda Putri; Muhammad Ario Permadi; Mukhtaruddin Mukhtaruddin (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to map the development of capital budgeting research with a focus on risk perception, project uncertainty, and investment appraisal techniques. A systematic literature review was conducted by integrating bibliometric analysis using Bibliometrix software on 101 articles retrieved from the Scopus and Dimensions databases. The analysis covers publication trends, author collaboration, and dominant research themes. The results indicate a significant increase in publications over the last decade, particularly in the areas of project risk management and advanced investment appraisal methods. The findings also reveal a thematic shift from traditional capital budgeting approaches toward risk- and uncertainty-based frameworks, along with the integration of non-financial factors in investment decision-making. This study provides a comprehensive overview of the evolution of capital budgeting research and offers a foundation for future studies as well as managerial practices that are more adaptive to risk and uncertainty.